Analisis Perhitungan Pada Harga Pokok Produksi Seragam Sekolah Dasar Merah Putih - Rizki Dwi Rama Setyawan; Setijanen Djoko Harijanto (Jurnal Sains dan Teknologi, 2023)
CV XYZ is a small and medium company engaged in garment business and headquartered at Jalan Abdurrahman no. 49 RT 15 RW 06, Pabean, Sedati, Sidoarjo. Various types of clothing are produced, such as red and white uniforms as one of its main products. CV XYZ in determining the cost of goods produced is only based on the assumption of the use of materials, tools and wages without considering the details. This situation makes it impossible for the company to know the actual cost of goods produced. This study aims to analyze the determination of production costs that can be used as a basis for effective assessment. The calculation of raw material costs, labor costs, processing costs and electricity costs according to the full cost method shows that production costs have increased compared to the company's provisions. The production cost of the women's red and white uniform is Rp 106,320 and the men's red and white uniform is Rp 108,134. Meanwhile, the price difference obtained for the women's white uniform is Rp 1,320 and the men's red and white uniform is Rp 3,134.